Remembering Mark Blaug - Bruce Caldwell (Duke University, Center for the History of Political Economy (CHOPE), 2012)
In the paper I offer some vignettes on my relationship, both professional and personal, with Mark Blaug, and by way of example reflect on his impact on the history of economics.
Keywords: B2; B31; B4; 330; Mark Blaug; history of economic thought; economic methodology; Karl Popper; falsificationism; Imre Lakatos